Volume 2: Combustion, Fuels and Emissions, Parts a and B 2011
DOI: 10.1115/gt2011-45362
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Turbulent Boundary Layer Flashback Limits for Premixed Hydrogen-Air Flames Confined in Ducts

Abstract: The design of flashback-resistant premixed burners for hydrogen-rich fuels is strongly dependent on reliable turbulent boundary layer flashback limits, since this process can be the dominant failure type for mixtures with high burning velocities. So far, the flashback data published in literature is based on tube burner experiments with unconfined flames. However, this flame configuration may not be representative for the most critical design case, which is a flame being already present inside the duct geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Since research on flashback began with the first systematic study by Lewis and von Elbe [1,2], the focus has been on measuring flashback limits in (non-swirling) Bunsen-flame type burners for many years [3][4][5][6][7], including more recent studies carefully testing additional parameters such as confinement, wall temperature and pressure [8][9][10][11][12][13]. High-speed optical diagnostics and advanced simulation tools have been applied more recently to reveal new information about the flame propagation dynamics [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Since research on flashback began with the first systematic study by Lewis and von Elbe [1,2], the focus has been on measuring flashback limits in (non-swirling) Bunsen-flame type burners for many years [3][4][5][6][7], including more recent studies carefully testing additional parameters such as confinement, wall temperature and pressure [8][9][10][11][12][13]. High-speed optical diagnostics and advanced simulation tools have been applied more recently to reveal new information about the flame propagation dynamics [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The flame holding behaviour is investigated as a function of injection geometrical configuration, fuel composition and injection angle (Grout et al 2011Kolla et al 2012). The former topic, focusing on the characteristics of the upstream propagation of premixed, preheated hydrogen (H 2 )-air flames in turbulent boundary layers, against the bulk flow direction, constitutes the main concern of the present DNSs and of a parallel experimental effort (Eichler, Baumgartner & Sattelmayer 2011; conducted in the framework of the BIGCO2 Project and of the BIGCCS International CCS Research Center (more information is available at http://www.bigccs.no).…”
mentioning
confidence: 99%
“…Nonetheless, the Blasius correlation is expected to provide a reasonably good estimation of the velocity gradient, as suggested in Ref. [15]. In contrast to g c , g f indicates the capability with which the flow can counteract the opposed propagation of the flame front.…”
Section: Flashback Criterion Based On Critical Velocity Gradients At mentioning
confidence: 95%
“…Specifically for the hydrogen-containing or hydrogen-rich mixtures, the issue of boundary layer flashback has been investigated in some recent studies [10,[13][14][15]. From the perspective of fuel compositions, it is found that the flashback behavior is dominated by the hydrogen content [10,16,17].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation